Use of magnetic techniques for the isolation of cells - Safarík, I; Safaríková, M (Journal of chromatography. B, Biomedical sciences and applications, 1999)
Magnetic separation is an emerging technology using magnetism, sometimes in combination with conventional separation or identification methods, to purify cells, cell organelles and biologically active compounds (nucleic acids, proteins, xenobiotics) directly from crude samples. Several magnetic separation procedures have been developed to isolate target cells specifically. The purpose of this short review is to summarize various methodologies, strategies and materials which can be employed for the selection and separation of target cells with the help of magnetic field and thus to help the novices in this field to be able to orient themselves in vast amount of literature available. Immunomagnetic separations employing specific antibodies to label the target cells represent the most often used approach and are discussed in detail.
Keywords: Cell Separation; Chromatography, High Pressure Liquid; imunomagnetická separace; elektronová mikroskopie; separace buněk; Microscopy, Electron; vysokoúčinná kapalinová chromatografie; Immunomagnetic Separation